1994
DOI: 10.1128/iai.62.6.2229-2235.1994
|View full text |Cite
|
Sign up to set email alerts
|

Entrance and survival of Salmonella typhimurium and Yersinia enterocolitica within human B- and T-cell lines

Abstract: Lymphocytes, located within the Peyer's patches, might be involved in the dissemination of enteropathogenic Salmonella typhimurium and Yersinia enterocolitica bacteria. To test this hypothesis, we have investigated the susceptibility of human Band T-cell lines to bacterial adhesion and invasion. The two S. typhimurium strains analyzed were highly invasive, while the two Y. enterocolitica (0:8) strains adhered to the Band T-cell lines but did not enter the cell lines in significant amounts. We hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Salmonella typhimurium proliferates inside several cell types, such as macrophages and epithelial cells, but not in lymphoid cells. 1,2 Spondyloarthropathies, including ReA, are strongly associated with the class I allotype human leucocyte antigen (HLA)-B27. 3 The pathogenetic role of this molecule remains unknown, but several hypotheses have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella typhimurium proliferates inside several cell types, such as macrophages and epithelial cells, but not in lymphoid cells. 1,2 Spondyloarthropathies, including ReA, are strongly associated with the class I allotype human leucocyte antigen (HLA)-B27. 3 The pathogenetic role of this molecule remains unknown, but several hypotheses have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms to alter regulation of immune and inflammatory responses, as demonstrated in murine macrophages, is to induce apoptosis by suppressing the cellular activation of NF‐kB, which in turn inhibits production of TNFα[11]. For human B and T cells, adherence of Yersinia , but not invasion, was found in significant amounts as well [12] .…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that B cells are targets of Salmonella infection. [22][23][24][25][26][27][28] In murine models, we observed that Salmonella…”
Section: Spi-5 Encodes a Series Of Proteins Responsible For Enteropatmentioning
confidence: 99%
“…22 In vitro assays have shown that human B cell lines JY and JP and mouse B cell line A20 are able to internalize bacteria. 24,26 Additionally, it has been reported that Salmonella typhi is able to infect the immortalized B lymphoblastoid cell line (LCL). The infection is macropinocytosis-dependent because the LCL treated with amiloride (a macropinocytosis inhibitor)…”
Section: Spi-5 Encodes a Series Of Proteins Responsible For Enteropatmentioning
confidence: 99%